Urban Agriculture and Quality of Life: A Comparative Analysis of Different Forms of Urban Agriculture and Its Effects on Welfare - Grobelnik Mlakar, Silva; Lankes, Maximilian; Trabucco, Elena; Chmelárová, Lenka; Molnar, Petra; Krasniqi, Amrush (Quality of Life in a Changing World: Spatial, Social and Environmental Perspectives from Maribor and Beyond, 2026)
This paper explores the diverse forms and functions of urban and peri-urban agriculture (UA/PUA) across six European cities—Bayreuth, Prishtina, Budapest, Venice, Brno, and Maribor—highlighting their contributions to social well-being, environmental sustainability, and community development. Drawing on literature review and field research, including interviews conducted in Maribor, the study analyses how UA strengthens local food systems, promotes ecological awareness, and enhances emotional and social resilience in urban communities. Comparative insights reveal that while UA initiatives share common goals of sustainability and inclusion, their success depends on tradition, local governance, institutional support, and civic participation. The Maribor case exemplifies how educational gardens, cooperatives, and community-supported agriculture (CSA) models can integrate learning, production, and social interaction. Overall, the findings suggest that UA serves not merely as a source of food but as a transformative social practice fostering connection, sustainability, and a sense of place in contemporary urban environments.